Eficiencia y eficacia de los servidores públicos de Distrito de educación 13D11 San Vicente- Sucre - Alcívar Pazmiño, Yandri Fabricio (2020)
Efficiency and effectiveness in public institutions are the main points to achieve the planned goals, properly use resources and offer quality services. For this reason, the objective of this research was to evaluate the efficiency and effectiveness of public servants of the 13D11 San Vicente - Sucre Education District for continuous improvement and organizational transformation. In this way, it began with bibliographic and field research, which allowed knowing the main concepts and obtaining information directly from the object of study. The Annual Operational Plan 2018 was analyzed in which the planned activities were identified annually, then an interview was conducted with the District Director to obtain information on the operation and planned activities, indicators were also applied to verify compliance and analyze the data obtained. Obtaining as a result insufficient budget for the execution of the activities, which is why these are carried out on a regular, good and rarely excellent basis, it was also found that there is no total participation in the POA by public servants, deficient provision of resources for vehicle maintenance, limited provision of resources for infrastructure maintenance, among others. From these results, actions were designed that allow continuous improvement and organizational transformation, as well as the optimal work performance of public servants.